Use of clinoptilolite zeolite to reduce Christmas Island rock phosphate use Zea mays cultivation on an acid soil - Hasbullah, Nur Aainaa; Ahmed, Osumanu Haruna; Kasim, Susilawati; Nik Ab. Majid, Nik Muhamad (Academic Journals, 2014)
This study was conducted to (i) Determine dry matter production, nutrients concentration, nutrients uptake and use efficiency of Zea mays by including clinoptilolite zeolite in the fertilization program of Zea mays planted on an acid soil and (ii) Determine the effect of including Clinoptilolite zeolite in the fertilization program of Zea mays on selected chemical properties of an acid soil. The effect of Clinoptilolite zeolite application with 75% of fertilizers (C2) and 100% fertilizers (C1) on soil chemical properties were statistically similar. Similar observation was made for dry matter production, nutrients concentration, nutrients uptake and nutrients use efficiency. These suggest that substituting 25% of N, P and K fertilizers with Clinoptilolite zeolite is more beneficial compared to 100% application of these fertilizers. Clinoptilolite zeolite strong affinity for monovalent cations ensured timely availability of P by exerting more soil exchange sites to occupy Al3+ and Fe2+.